2020
DOI: 10.1200/jco.2020.38.15_suppl.e15135
|View full text |Cite
|
Sign up to set email alerts
|

Impact of STK11 and KRAS co-mutations on outcomes with immunotherapy in non-small cell lung cancer.

Abstract: e15135 Background: While the use of monoclonal antibodies targeting the PD-1 axis in metastatic non-small cell lung cancer (NSCLC) continues to expand since initial FDA approval in 2015, factors predictive of response still remain to be determined. Mutation status may provide insight as to which subgroups exhibit resistance to checkpoint inhibitor therapy. Methods: We conducted a single center retrospective analysis of patients with metastatic NSCLC treated at the University of Miami / Sylvester Comprehensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Several studies associated STK11/KRAS co-mutation with worse progression-free survival and overall survival after ICI treatment of NSCLC. [13][14][15][16] In this study we aimed to test whether STK11/KRAS co-mutation plays a predictive role in response to ICI or not, in an observational real-world pan-cancer cohort.…”
Section: Impact Of the Stk11/kras Co-mutation On The Response To Immu...mentioning
confidence: 99%
“…Several studies associated STK11/KRAS co-mutation with worse progression-free survival and overall survival after ICI treatment of NSCLC. [13][14][15][16] In this study we aimed to test whether STK11/KRAS co-mutation plays a predictive role in response to ICI or not, in an observational real-world pan-cancer cohort.…”
Section: Impact Of the Stk11/kras Co-mutation On The Response To Immu...mentioning
confidence: 99%
“…STK11 mutations in NSCLC may be associated with worse outcomes with ICIs since the inactivation of this serine threonine kinase involved in various cellular functions is associated with a low T lymphocytes tumor infiltration and a “cold” tumor microenvironment ( 21 , 22 ). However, it is not clear whether the impact of STK11 mutations is predictive of poor response to ICIs specifically, or simply prognostic of aggressive tumor evolution ( 23 25 ). Furthermore, in an exploratory analysis of the KEYNOTE-042 trial comparing single-agent pembrolizumab to chemotherapy, STK11 mutations did not appear to impact the efficacy of ICIs, while they were associated with a worse prognosis in the chemotherapy cohort ( 26 ).…”
Section: Main Mechanisms Of Resistance and Definitionsmentioning
confidence: 99%
“…In contrast, transversion mutations (substitution of a purine by a pyrimidine or vice versa) in the Ki-ras2 Kirsten rat sarcoma viral oncogene homolog ( KRAS ) gene and tumor suppressor gene TP53 alone predicted better outcomes [ 69 ]. Another study reported that NSCLC patients on anti-PD-1 IO who harbored co-mutations of STK11 and KRAS ( n = 36) detected in ctDNA had longer OS in comparison to patients who harbored STK11 mutations alone (13.6 ± 3.4 months, p = 0.049, n = 37) [ 70 ]. The OAK and POPLAR clinical trials showed that mutations in the kelch-like ECH-associated protein 1 ( KEAP1 ) and nuclear factor erythroid-2-related factor-2 ( NFE2L2 ) genes detected in ctDNA were associated with poorer OS and PFS (OS: HR = 1.7, p < 0.001; PFS: HR = 1.4, p < 0.001) in NSCLC patients receiving IO [ 71 ].…”
Section: Circulating Tumor Dna (Ctdna)mentioning
confidence: 99%